Differentilalumgebung dritter Ordnung des Strahlenkomplexs - Grincevičius, K. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:К. Гринцевичюс. О дифференциальной окрестности третьего порядка комплекса прямыхK. Grincevičius. Apie tiesių komplekso trečios eilės diferencialinę aplinką